Haploinsufficiency of insulin gene enhancer protein 1 (ISL1) is associated with d‐transposition of the great arteries - Kazutoyo Osoegawa; Kathleen Schultz; Kenneth Yun; Nebil Mohammed; Gary M. Shaw; Edward J. Lammer (Molecular Genetics & Genomic Medicine)
Abstract Congenital heart defects are the most common malformation, and are the foremost causes of mortality in the first year of life. Among congenital heart defects, conotruncal defects represent about 20% and are severe malformations with significant morbidity. Insulin gene enhancer protein 1 (ISL1) has been considered a candidate gene for conotruncal heart defects based on its embryonic expression pattern and heart defects induced in Isl1 knockout mice. Nevertheless no mutation of ISL1 has been reported from any human subject with a heart defect. From a population base of 974,579 births during 1999–2004, we used multiplex ligation‐dependent probe amplification to screen for microdeletions/duplications of ISL1 among 389 infants with tetralogy of Fallot or d‐transposition of the great arteries (d‐TGA). We also sequenced all exons of ISL1. We identified a novel 20‐kb microdeletion encompassing the entire coding region of ISL1, but not including either flanking gene, from an infant with d‐TGA. We confirmed that the deletion was caused by nonhomologous end joining mechanism. Sequencing of exons of ISL1 did not reveal any subject with a novel nonsynonymous mutation. This is the first report of an ISL1 mutation of a child with a congenital heart defect.